2007
DOI: 10.1167/iovs.06-1278
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Enhanced MRI Studies of Alterations of Intraretinal Ion Demand in Models of Ocular Injury

Abstract: MEMRI measurements of uptake of systemically administered and nontoxic doses of manganese appear to be a powerful approach for measuring alteration in intraretinal ion demand in models of ocular injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 39 publications
7
66
0
Order By: Relevance
“…600 mm). We have experimentally confirmed that a resolution of 10 pixels or less across the retina is not substantially contaminated by the choroidal circulation, which can arise from partial-volume averaging (see below) (9). In addition, rat and mouse studies can use similar acquisition parameters because retinal thickness in rats and mice is comparable despite the difference in ocular diameter of roughly a factor of two (6 cm in rats and 3 cm in mice) (10).…”
Section: Retinal Anatomy and Mrisupporting
confidence: 58%
See 1 more Smart Citation
“…600 mm). We have experimentally confirmed that a resolution of 10 pixels or less across the retina is not substantially contaminated by the choroidal circulation, which can arise from partial-volume averaging (see below) (9). In addition, rat and mouse studies can use similar acquisition parameters because retinal thickness in rats and mice is comparable despite the difference in ocular diameter of roughly a factor of two (6 cm in rats and 3 cm in mice) (10).…”
Section: Retinal Anatomy and Mrisupporting
confidence: 58%
“…The accuracy and sensitivity of these MRI measurements, relative to standard physiological approaches, have also been validated (8,14,(16)(17)(18)(19)(20). Many of the metrics summarized in Table 1 do not perturb retinal physiology and have been successfully applied to the study of normal and altered retinal health (Table 2).…”
Section: What Aspects Of Retinal Physiology Can Mri Evaluate?mentioning
confidence: 99%
“…To ensure that we are measuring from IR and OR, regions 3 pixels posterior to the retina/vitreous border and 4 pixels anterior to the retina/sclera border (both borders are easily observed) were analyzed to sample the IR and OR, respectively, as described previously (51). To measure retinal thickness, we used in-house written software to first map the in situ image into a linear representation for each retina, as described previously (52). The linearized data from each hemiretina between 0.4 and 1 mm from the optic nerve were binned.…”
Section: Methodsmentioning
confidence: 99%
“…Manganese doses that have been used for brain activity mapping in awake and behaving rodents (e.g. 66 mg/kg for rats and 64 mg/kg for mice) have been considered as non-toxic because they produced no or minimal side effects detected in rodent general behavior (Berkowitz et al, 2006;Berkowitz et al, 2007;Bissig and Berkowitz, 2009;Yu et al, 2005). Berkowitz and colleagues reported no retinal toxic effects after a single systemic injection of MnCl 2 assessed by number of histological, physiological and electrophysiological indices (Berkowitz et al, 2006;Berkowitz et al, 2007).…”
mentioning
confidence: 99%
“…66 mg/kg for rats and 64 mg/kg for mice) have been considered as non-toxic because they produced no or minimal side effects detected in rodent general behavior (Berkowitz et al, 2006;Berkowitz et al, 2007;Bissig and Berkowitz, 2009;Yu et al, 2005). Berkowitz and colleagues reported no retinal toxic effects after a single systemic injection of MnCl 2 assessed by number of histological, physiological and electrophysiological indices (Berkowitz et al, 2006;Berkowitz et al, 2007). In our recent study, we found that corticohippocampal neurotransmission was weakened following MnCl 2 acute systemic administration in a dose of 80 mg/kg, while overall neuronal excitability and synaptic plasticity in the dentate gyrus of the hippocampal formation were not affected (Eschenko et al, in press).…”
mentioning
confidence: 99%